Technology or phenomenon: Why blockchain is not a technology - Byunguk Lee (Administrative Sciences, 2025)
Blockchain was introduced in 2008, yet it remains poorly defined over a decade later. Despite the lack of a universally accepted definition, its utility continues to be widely advocated. However, a function or feature can only be classified as a technology if it addresses a specific human discomfort. A mere combination of ambiguous functionalities without a clear purpose cannot be considered a technology. This paper investigates whether blockchain is an appropriate term for a specific technology or merely an ambiguous amalgamation of features. It further argues that technologies with analogous functionalities should be classified as distinct technologies if their applications differ. Through a literature review of the criteria for defining a technology, this paper finds that blockchain does not meet these requirements. Additionally, existing definitions of blockchain often fail to meet proper criteria or inaccurately describe its functionality. In the academic context, the term "blockchain technology" is a clear misnomer that should be discouraged. The findings can guide decision making for stakeholders, including companies, regulators, and legislators involved in the virtual asset market.
Keywords: 350; blockchain; definition; feature; function; human discomfort; technology